Identification and rejection of pile-up jets at high pseudorapidity with the ATLAS detector (vol 77, 580, 2017) - Aaboud, M.; Aad, G.; Abbott, B.; Abdallah, J.; Abdinov, O.; Abeloos, B.; Çetin, Serkant Ali (Springer, 2017)
[Abstract Not Available]